Clinical Implications of Complex Pharmacokinetics for Daratumumab Dose Regimen in Patients With Relapsed/Refractory Multiple Myeloma. Issue 6 (13th February 2017) - Xu, XS; Yan, X; Puchalski, T; Lonial, S; Lokhorst, HM; Voorhees, PM; Plesner, T; Liu, K; Khan, I; Jansson, R; Ahmadi, T; Ruixo, JJ Perez; et al.
Abstract : New therapeutic strategies are urgently needed to improve clinical outcomes in patients with multiple myeloma (MM). Daratumumab is a first‐in‐class, CD38 human immunoglobulin G1κ monoclonal antibody approved for treatment of relapsed or refractory MM. Identification of an appropriate dose regimen for daratumumab is challenging due to its target‐mediated drug disposition, leading to time‐ and concentration‐dependent pharmacokinetics. We describe a thorough evaluation of the recommended dose regimen for daratumumab in patients with relapsed or refractory MM.